O processo de construção do conhecimento por meio das novas tecnologias no contexto da conexão sem fio - Ono, Arnaldo Turuo (2010)
It is intended through this study to understand how individuals construct knowledge using new technologies, considering the context of wireless connections. As a first step, a literature research in online electronic databases was carried out in order to identify the state of the art , regarding the subject, in different countries, besides Brazil. Next, the theoretical reference was composed, covering concepts related to technology, learning, knowledge, and the model of Learning Spiral Valente (2002) and theoretical model of Knowledge Creation Nonaka and Takeuchi (2003), which served as basis for the preparation of a proposal of inter-relationship between the two models. Taking this framework as a guideline, a qualitative field research was developed. Through interviews in depth, 65 subjects in three different groups were interviewed. Applying the technique of content analysis (BARDIN, 2004) and the Tree Similarities Technical analysis via CHIC (COUTURIER; BODIN; GRAS, 2003) the data were analyzed. The results pointed to situations in which individuals construct knowledge in different ontological stages in line with the proposed inter-relationship. There are also signs of a strong element of intentionality when the engagement of these individuals in virtual communities and development of collaborative works. This situation is not perceived in relation to ordinary users, who do not have specific interests. Another point that stands out was that new technologies do not replace existing ones, indeed those are included because of its features and capabilities, preserving and providing knowledge built through the new features, the refurbishment and construction of new knowledge. The issue of mobility appears to be unremarkable, because there are difficulties related to acquisition and maintenance high costs problems, issues regarding ergonomics (small keyboards and displays, in addition to increased volatility on the technological development of these devices. Thus, the contribution of this study was performed by means of the proposed inter-relationship between the Spiral of learning (VALENTE, 2002) and Theory of Knowledge Creation (NONAKA; TAKEUCHI, 2003); the application of two techniques for qualitative analysis data, content analysis (BARDIN, 2004) and CHIC (COUTURIER; BODIN; GRAS, 2003); and the results obtained from interviews with three distinct groups of individuals who use new technologies in the context of wireless wire, to achieve various levels of knowledge construction